English for tour guide program to improve English Skills of tour guides in Trenggalek’s Tourist Villages - Dwi Wahyuningtyas; Ria Arista Asih; Dessy Maeyangsari; A. R. Alyaa' Chiquita Fairuzara; Fredik Yunior Heuvelman; Roro Millatu Al-Ghaniy (Universitas Muhammadiyah Malang, 2022)
Trenggalek is one of the potential regencies in East Java, with many beautiful tourist destinations. Realizing this fact, the government of Trenggalek has set a target to develop 100 tourist villages in Trenggalek by 2024. Tourist villages are now becoming one of the main attractions in Trenggalek. To make the villages more known and visited by tourists, some support is needed, one of which is the involvement of tour guides skilled in using English. Therefore, the community service team from UPN